PROSPECTS FOR THE USE OF SAFFLOWER (CARTHAMUS TINCTORIUS L) IN OPHTHALMOLOGY - Rakhimov K.D.; Abuova Zh.B.; Turgumbayeva A.A. (Academic Journal of Physical and Chemical Sciences, 2020)
Plant materials and preparations based on it continue to play an important role in the pharmacotherapy of many chronic and sluggish human diseases. Over the past two decades, there has been a very high consumer demand for medicines and preventive products obtained from natural plant sources. This is due to the complex effect of biologically active substances, vitamins, antioxidants of plant origin on the human body and the practical absence of side effects. An analysis of the development of phytopharmacology shows that the most promising direction in the field of the development of phytopreparations is the scientifically based use of the experience of traditional and modern medicine. One of the promising types of raw material - medicinal plant safflower (Carthamus tinctorius L). It contains vitamins A, E, unsaturated fatty acids and other biologically active substances in large quantities, that determine antimicrobial, antifungal, anti-inflammatory, antioxidant properties. Thanks to these pharmacological effects, the content of vitamins is promising for the development and introduction of a drug used in the field of ophthalmology. To this end we have searched and analysed scientific publications about safflower – Carthamus tinctorius. All studies used in this review have been found using «Google Scholar» scientific search engine and were selected from publications indexed in Web of science, PubMed, Medline, E–library, and Cyberleninka databases.